'If they do it, so can I': a test of a moderated serial mediation model of descriptive norms, self-efficacy, and perceived similarity for predicting physical activity. Issue 6 (14th June 2021) - Kim, Jeemin; Eys, Mark; Robertson-Wilson, Jennifer
Abstract: Objective: Though engaging in physical activity (PA) is associated with several health benefits, physical inactivity rates remain high. Previous research revealed that descriptive norms (i.e., perceptions of others' PA) positively relate to PA intentions/behaviours. This study tested whether self-efficacy mediated the influence of descriptive norms on PA intentions and behaviours, and whether the relationship between descriptive norms and self-efficacy was moderated by perceived similarity with normative referents. Design: Online questionnaires were administered. Measures: Baseline measures included descriptive norms, perceived similarity, self-efficacy, and PA intentions. Weekly PA behaviour frequency was assessed at baseline and two weeks post-baseline. Results: Descriptive norms positively predicted PA behaviour frequency at time 2 indirectly via self-efficacy and PA intentions. These indirect effects were attenuated when baseline PA behaviour frequency was accounted for. There was no support for perceived similarity as a moderator, which may be attributed to a potential ceiling effect or the nature of items used to assess this perception. Conclusion: The findings support the notion that individuals may feel more efficacious when they perceive that others are successfully engaging in the targeted task/activity. Future interventions may consider providing descriptive norm messages to individuals who lack self-efficacy or previous PA experience to promote their PA.